Educational technology for people living with HIV: validation study - Gisele de Brito Brasil; Ivaneide Leal Ataíde Rodrigues; Laura Maria Vidal Nogueira; Iaci Proença Palmeira
ABSTRACT Objective: to validate an educational technology to support the action of health professionals with people living with HIV. Method: methodological study with data collection using a four-point Likert scale for evaluation by eleven judges and 51 people living with HIV. The data were tabulated, processed, and analyzed by inferential and descriptive statistics, Cronbach's alpha test, and Kruskal-Wallis for reliability and internal consistency analyses. Result: the Cronbach's alpha was 0.974 for judges and 0.694 for the target audience, reliable values. Kruskal-Wallis tested hypotheses H0 and H1 with significance of 0.05. H0 was accepted with significance of 0.395 for judges and 0.187 for the target audience, demonstrating agreement on the distribution of answers. Judgements with favorable response of at least 70% were considered relevant, according to the performed tests. Conclusion: the technology presents high reliability and good internal consistency, being deemed appropriate.